Modern Business Environment and Environmental Scanning - Neelameghan, A. (Journal of Information and Knowledge, 1975)
The environment of modern business is dynamic and influences business in a variety of ways increasingly, a company finds itself drawn into interaction with many other companies in different sectors, and a variety of social-industrial complexes Political, social, legal, economic, and technological factors at the unit, local, national, regional, and international levels affect the affairs of the company. The company needs to have up-to-date information about these factors if it is to make precise forecasts, gainful decisions, integrated plans and operate at a competitive level. It has also to be aware of the emerging new economics of information.